Indoor environmental quality and energy cost saving prediction model for radiantly cooled slab tropical buildings - Kwong, Qi Jie (2014)
The building sector is one of the major energy users. This has made efficient energy utilisation in buildings a necessity in conserving the fast-depleting resources and to achieve reduction in energy cost. Efficient use of energy consuming devices such as air-conditioning and artificial lighting systems in buildings is therefore essential for energy efficiency improvement. This research aims to evaluate the indoor environmental quality (IEQ) of a Malaysian building that was cooled via a combination of radiant and convective systems and to compare the energy performance of this apparatus to a conventionally designed all-air system. Field assessments which consisted of physical and subjective (questionnaire) assessments were conducted to measure the current IEQ levels as well as to identify the occupants’ perception on their immediate surroundings. The energy management system was used to gather energy consumption data of the building under study. The outcomes demonstrated that the measured IEQ parameters were within acceptable ranges except for the air velocity profile. From the subjective measurement, 83.3% of the occupants were satisfied with their thermal environment and 59.5% of the votes were placed within the three central categories of the thermal sensation scale. Besides, each environmental comfort factor exerted different level of impact towards the occupants’ work productivity. Natural daylight was found to be sufficient in providing a visually comfortable environment to occupants during peak working hours, while occupants were generally more tolerant towards the acoustical condition. The air quality was perceived as acceptable for 92% of the occupants, which was consistent with the measured air contaminants’ levels. The operative temperature was calculated by using the measured air temperature and mean radiant temperature and a neutral operative temperature of 25.4 °C was obtained. An adaptive coefficient of -1.1262 was subsequently calculated which showed the level of thermal adaptation among the occupants. Besides, it was found that the combined radiant-convective system was able to reduce the energy cost for air-conditioning of interior spaces by 42.5%. A simple payback period of 5.3 years was calculated by considering all the associated costs. The outcomes of this study also suggested that more energy savings without compromising human comfort can be obtained by raising the thermostat setting to 2 °C higher than the conventional setting and the use of natural daylight during working hours. Further studies on evaluating the IEQ conditions of other tropical buildings that are using radiant cooling systems and application of automatic window shades for daylight control were suggested.